2008
DOI: 10.1038/cdd.2008.45
|View full text |Cite
|
Sign up to set email alerts
|

Brn-3a/POU4F1 interacts with and differentially affects p73-mediated transcription

Abstract: The Brn-3a/POU4F1 POU transcription factor is critical for the survival and differentiation of specific sensory neurons during development or upon injury; by regulating expression of target genes, either directly or indirectly upon interaction with other proteins. In this study, we demonstrated the physical interaction of Brn-3a with different p73 isoforms and showed co-localization in sensory neurons arising from the neural crest. The biological effects of p73/ Brn-3a interaction depend on the particular p73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous studies of POU4F1 have been restricted to neuronal cells, where it has been shown to promote cell survival and inhibit apoptosis, in part by antagonizing p53 and p73 to increase Bcl2 and Bax expression (44, 45). In hematopoietic cells, we observed different effects of Pou4f1 on transcription and cell growth (in fact, Pou4f1 appears to restrain cell growth that was stimulated by AE).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of POU4F1 have been restricted to neuronal cells, where it has been shown to promote cell survival and inhibit apoptosis, in part by antagonizing p53 and p73 to increase Bcl2 and Bax expression (44, 45). In hematopoietic cells, we observed different effects of Pou4f1 on transcription and cell growth (in fact, Pou4f1 appears to restrain cell growth that was stimulated by AE).…”
Section: Discussionmentioning
confidence: 99%
“…3c, Supplementary Table 1 ). TP73 has been shown to regulate NPC proliferation in the developing and adult mouse central nervous system 38,39 and is known to interact via its subdomains with many different partner proteins, including POU 40 which has corresponding motifs in this region and YAP1, which is known to function as both an activator or repressor 41 in a context dependent manner 42 . These instances demonstrate that FRSs can achieve their desired transcriptional rate by combining both activating and repressive motif sites, and that using our perturbation MPRA approach allowed us to distinguish the functionality in each specific context.…”
Section: Resultsmentioning
confidence: 99%
“…Isl2 was down-regulated by 55% after ON, and the p -value was 0.000594. The transcription factor Pou4f1, also named Brn3a, was another negative regulator of apoptotic process (Hudson et al, 2008 ; Dykes et al, 2010 ). Pou4f1 was down-regulated by 51% after ON and the p-value was 2.16 × 10 −8 .…”
Section: Resultsmentioning
confidence: 99%